Public and Private Welfare State Institutions: A Formal Theory of American Exceptionalism - Kaj Thomsson (Research Institute of Industrial Economics (IFN), 2010)
I construct a model of public policy development, and use the model to explain why the United States has a comparatively small public sector, but instead a large private welfare state with employment-based benefits. The key factors are politically organized firms and labor unions. These interest groups can use campaign support to influence a political decision-maker who decides whether to implement a social benefit. In addition, the firms can influence the outcome indirectly by privately providing their own workers with the benefit. This setup leads to three possible outcomes. In the first, no one is provided the social benefit. In the second, all workers receive it through government provision. In the third, some workers receive the policy, through their employers. I argue that the features leading to the third equilibrium correspond closely to political institutions and industry characteristics of the US, while the features of the second equilibrium better describe European countries.
Keywords: D72; D78; H11; H50; N42; P51; 330; Political Economy; Interest Groups; Institutions; Welfare States